Operational costing of inpatient orthopaedic services at the Helen Joseph Hospital - Bogoshi, Gladys Magugudi (My University, 2012)
BACKGROUND: Until recently budget allocation for public hospitals in the Gauteng Province were based on the historical values and not on the costed activities. It is therefore unknown how much of the allocated budget is used per discipline in an institution. Because of recurrent over expenditure by institutions, Gauteng Department of Health and Social Development have decided to change policy for budget allocation of funding public health facilities from historical allocation to activity based costing. Although good financial management of hospitals is a priority for the government, data on real costs of providing health care services is scarce and unreliable. No formal study has been done to estimate the cost to provide inpatient services in the Helen Joseph Hospital, a regional hospital in the Gauteng Province. In view of that, it was decided to initiate this study at the Orthopaedic unit of the Hospital, which would then be extended to the other units. AIM: To estimate the caseload, profile of patients and operational cost of providing the inpatient orthopaedics services at a regional hospital in Gauteng. METHODOLOGY: A cross-sectional study design was used based on retrospective review of patients’ and hospital records of patients admitted during one month study period at the two Orthopaedic Ward in the Helen Joseph Hospital, situated in the Johannesburg Health District in the Gauteng Province. RESULTS: Total number of patients admitted in the Orthopaedic Unit of the Hospital in the year 2009/2010 was 2160 (The mean number of inpatients per month was 180 ± 28). Profile of patients One hundred and ninety seven patients were admitted during one month study period. There were more male than female patients. The median age was 41 years (IQR 31-53 years). More black patients were admitted during this period, even though the main catchment population for the Hospital is predominantly white and coloured. The majority of patients were from a low socio-economic class as reflected by their classification for user fee payment using the means test. The median inpatient day was 3. The most common cause of admissions is due to injury, poisoning and certain other consequences of external causes as expected in an Orthopaedic Ward. A low complication rate (4.5%) was found to be the lowest as compared to other units in the Hospital. The majority of patients were discharged. Cost drivers The major cost driver was human resource which accounted for 70% of the total expenditure. Other cost drivers were material resources used in the unit, which includes: laboratory, blood and blood products, radiology and pharmaceuticals. Expenditure on these items account for only 13.7% of total expenditure. Cost driver Amount Unit cost Laboratory R61,215.57 R412.26 Blood and blood products R53,164.41 R269.87 Radiology R52,085.50 R264.39 Pharmaceuticals R17,315.82 R87.90 The total expenditure during this period was R 1,481,363.30 or R 17,776,359.60 annually. The unit cost of laboratory services (Ward 4: R926.30 and Ward 5: R272.97), blood and blood products (Ward 4: R463.05 and Ward 5: R217.52), radiology (Ward 4: R659.97 and Ward 5: R157.20) and pharmaceuticals (Ward 4: R236.63 and Ward 5: R47.60) and varied significantly between Ward 4 and Ward 5 which might be due to difference in clinical practices between the two Wards. CONCLUSION: This study showed the operational costs needed to provide an inpatient orthopaedic service at a regional health facility. Further study based on more detailed costing at individual patient level is necessary to develop a better understanding of costing at these Wards. This study highlighted the significance of understanding the importance of determining the actual costs needed to provide an inpatient service in a health facility. Simple cost analysis method could easily be done at Unit/ Ward level to provide more insight to Hospital managers who are always criticized for overexpenditure.
Keywords: Orthopedics; Costs and Cost Analysis